PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DALAM MEMBENTUKLOYALITAS PELANGGAN PADA CLINICNATASHASKIN CARE MEDAN - Sirait, Mariyanti; Syamsuri, Abd. Rasyid (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2014)
This research aims to determine the effect of service quality for customer satisfaction in forming customer loyalty in Clinic Natasha Skin Care Medan.This type of research is quantitativeresearch.The sampling technique using incidental sampling method.The type of data used are primary data and secondary data.Data analysis techniques used in this research is descriptive analysis, multipleanalysisregression, hypothesis testing using simultaneous significant test (test F), significant testing partially (ttest), and testing the coefficient of determination (R2 ). These results indicating that together for a positiveand significantinfluence between service qualityfor customer satisfaction in forming customer loyalty in Clinic Natasha Skin Care Medan.The partial test (t test) note that variables and service service quality for customer satisfaction in forming customer loyalty in Clinic Natasha Skin Care Medan. While the variablecustomer satisfaction no effect dan significant impact on the purchase decisionat Clinic Natasha Skin CareMedan. Through testing ajusted adjusted coefficient of determinationR Square of 0.528 means that 52.8% factors service quality and customer satisfactioncan be explained by other factors which arent pursuing by other researcherpact and significantly to customer loyalty.